PENATALAKSANAAN FISIOTERAPI PADA KONDISI TENDINITIS SUPRASPINATUS DEXTRA DENGAN MODALITAS ULTRASOUND, MYOFACIAL RELEASE DAN TERAPI LATIHAN DI RSUD BENDAN KOTA PEKALONGAN - Muhammad Yusron; Irine Dwitasari Wulandari (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2016)
Supraspinatus tendinitis is inflammation of the supraspinatus tendon. The purpose of riset is to understand the implementation of physiotherapy in reducing pain, reducing muscle spasm, improving muscle strength, increase range of motion and increase the ability of functional activityin the supraspinatus tendinitis condition with ultrasound modality, myofacial release and exercise therapy. This research was carried out in Bendan District Hospital Pekalongan with descriptive analytic methods. Once done six times therapy, results obtained the presence of pain reduction i.e. silent pain T1 = 1 at the T6 = 0, tenderness T1 = 3 T6 = 1, pain motion T1 = 7 at T6 = 3, decrease muscle spasm T1 = 1 at the T6 = 0. The increased range of motion in the active movement. Increasing the scope of the joint motion on the active and passive movement. On increasing muscle strength, namely the abductor muscles T1 = 3 at T6 = 5. Improving the ability of functional activity, i.e.: T1 = 63,07 at T6 = 40,76. Interventions physiotherapy using ultrasound modality, myofacial release and exercise therapy can help reduce the problems that arise on the condition of the supraspinatus tendinitis